Albedo method applied for gamma radiation shielding - Augusto Elizandro de Aguiar; Ronaldo Glicério Cabral; Claudio Luiz de Oliveira; Sérgio de Oliveira Vellozo (Brazilian Journal of Radiation Sciences, 2023)
Mathematical tools for calculating radiation shielding usually have difficult notations that could only be solved by computational methods. The Albedo’s method applied for calculation of shielding proves to be an excellent substitute in determining the incident beam fractions that are reflected, absorbed and transmitted, avoiding the use of the transport equation and diffusion approximation that are extremely important in nuclear reactor designs and irradiation calculations. Based on the simple following of the radiation current path, the method can be characterized as a graphical and analytical solution. This work explores the Albedo’s Method applied to 4-slab shielding with incidence of gamma radiation to an energy group compared to ANISN, computational method consecrated in the area of ​​nuclear calculations.